THE CRUCIAL ROLE OF PALLIATIVE CARE IN ADVANCED BREAST CANCER - Goncalves, Graziella Galvão (Revista Sistemática, 2024)
Palliative care is a crucial component in the treatment of breast cancer patients, particularly in advanced or metastatic stages, when curative treatments lose their effectiveness. The main focus of palliative care is not only the relief of intense physical symptoms, such as pain and fatigue, but also providing psychological and emotional support, enhancing the quality of life for both the patient and their family. A multidisciplinary approach allows for holistic care that respects the patient’s choices, offering a more humane and personalized care experience. Research highlights the importance of early interventions, such as palliative care consultations, which can improve treatment adherence and reduce negative emotional impacts like anxiety and depression. Additionally, educational programs are essential for raising awareness about the benefits of palliative care. However, significant challenges remain, such as limited access to palliative care in regions with inadequate infrastructure and the need for further training of healthcare professionals. The implementation of public policies and specific palliative care protocols is crucial to ensuring that all breast cancer patients, regardless of disease stage or location, receive the necessary support to live with dignity and comfort until the end of their journey.